(untitled) (Research, Society and Development, 2021)
This work produced coating mortars with scheelite tailings (ST) in total replacement of natural sand aggregate. The chemical and mineralogical composition of the scheelite tailings was determined by X-ray diffraction (XRD) and X-ray fluorescence (XRF). Mortar samples with a mass proportion of 1:2:9 (cement: lime: sand/scheelite tailings) were prepared with and without the scheelite tailings. The mortars were evaluated by mercury intrusion porosimetry and compressive and flexural strength tests. The resistance to the alkali-aggregate reaction was assessed from the bar expansion test and by scanning electron microscopy (SEM) in the crack and pore regions. The results indicate that until the 22nd day, the scheelite tailings were not reactive; however, in 28 days, the expansion was deleterious. SEM images did not detect the presence of amorphous alkaline gel characteristic of the alkali-aggregate reaction. Therefore, although the mortar with scheelite tailings aggregate has shown the deleterious potential to 28 days, mechanical tests indicate that it has the potential to be used as a coating mortar.